Stability and Activity of Doped Transition Metal Zeolites in the Hydrothermal Processing - Robin, Thomas François; Ross, Andrew B.; Lea-Langton, Amanda R.; Jones, Jenny M. (Frontiers in Energy Research, 2015)
This study investigates the stability and activity of HZSM-5 doped with metals such as molybdenum, nickel, copper and iron in under hydrothermal conditions used for the direct liquefaction of microalgae. Catalysts have been prepared by ion exchange techniques, and MoZSM-5 was also prepared by wet incipient impregnation for comparison. Hydrothermal liquefaction is considered as a potential route to convert microalgae into a sustainable fuel. One of the drawbacks of this process is that the bio-crude produced contains significant levels of nitrogen and oxygen compounds which have an impact on the physical and chemical propriety of the fuel. Heterogeneous catalysts have been shown to improve the quality of the bio-crude by reducing nitrogen and oxygen contents. Zeolites, such as HZSM-5, are strong candidates due to their low cost compared to noble metal catalysts but their stability and activity under hydrothermal conditions is not well understood. The stability of the catalysts has been determined under hydrothermal conditions at 350 °C. Catalysts have been characterised before and after treatment using XRD, BET physisorption and STEM microscopy. Metal leaching was determined by analysis of the water phase following hydrothermal treatment. The inserted cation following ion-exchange can influence the physical properties of HZSM-5 for example molybdenum improves the crystallinity of the zeolite. In general, metal doped zeolites were relatively stable under subcritical water. Activity of the catalysts for processing lipids, protein and microalgae has been assessed. Four feedstocks were selected: sunflower oil, soya proteins, Chlorella and P. ellipsoidea. The catalysts exhibited greater activity towards converting lipids for example MoZSM-5 enhanced the formation of aromatic compounds. NiZSM-5 and CuZSM-5 were observed to be more efficient for deoxygenation.